WACANA DAN RELASI KUASA DALAM PENGELOLAAN DESTINASI WISATA DESA (STUDI KASUS BUMDES MAJU MANDIRI DAN OPERATOR GOA PINDUL) - Rina Widiastuti; Ghifari Yuristiadhi Masyhari Makhasi (Sekolah Vokasi Universitas Gadjah Mada, 2019)
This article discusses the power relations between BUMDes Maju Mandiri and the operator of a tourist attraction in Goa Pindul, Bejiharjo Village, Karangmojo District, Gunungkidul Regency. Using critical discourse analysis, the concept of development and relations between institutions was identified to determine the intertextuality and congruence of discourse between BUMDes Maju Mandiri and Goa Pindul operators. The results showed that the new BUMDes Maju Mandiri and Goa Pindul operators had different values, concepts, and attitudes in the management of Goa Pindul to cause ongoing conflict. The concluding section presents suggestions for improving power relations between the two parties and the importance of research to dismantle hidden power relations in tourist destinations.